Implementasi dan critical success factor manajemen risiko di instansi Pemerintah - Jauhari, Rifqie; Sukmadilaga, Citra; Mulyani, Sri (Jurnal Paradigma Ekonomika, 2021)
The development of risk management is not only for the private sector, the Ministry of Finance is one of the public sector organizations that has implemented risk management. The purpose of this research is to analyze risk management implementation process and its critical success factors in government agencies, particularly Ministry of Finance. This research uses a qualitative research method with a case study approach. Data collection was carried out by field research and literature study. Data analysis was performed using the Miles & Huberman data analysis model. The findings indicated the development of risk management in the Ministry of Finance as well as the critical success factors that affects the development of risk management. Of the 8 critical success factors identified, strong management commitment & leadership as well as risk management knowledge are required by government agencies when implementing risk management. Strengthening management commitment & leadership as well as risk management knowledge may facilitate government agencies in implementing risk management. Â